Something fishy: an unusual Erysipelothrix rhusiopathiae infection in an immunocompromised individual. (3rd April 2013) - Sinclair, Marie; Hawkins, Angela; Testro, Adam
Abstract : A 39-year-old man with a history of Crohn's disease presented to the emergency department with a 12-h history of worsening febrile illness. He deteriorated rapidly with progression to sepsis and was admitted to the intensive care unit. Initial treatment comprised broad spectrum antibiotics and inotropic support resulting in rapid improvement. With the immunocompromised state of the patient, and multiple blood cultures revealing Erysipelothrix rhusiopathiae, a detailed history disclosed a recent injury sustained from a fishing wire as the probable source of an infection. Treatment was narrowed to target the identified pathogen, the patient made a full recovery, and was counselled to be more cautious in future fishing activities.